The Influence of the Flowering Period Before the Second Harvest on the Productivity of Beda Collection Samples - Khudoyberdiev Nurali, Khudoyberdievich; Allashov Bakhrom Davletbaevich (Zien Journals, 2022)
The research work was carried out at the Research Institute of Agrotechnologies of breeding, seed production and cotton cultivation. The alfalfa collection presents the results obtained by studying the economic characteristics of alfalfa samples stored for 1 year, on the effect of the flowering period before the second harvest on productivity. The collection of samples collected from different continents and countries contains about 6 thousand samples of alfalfa. The creation and selection of new starting materials and varieties by studying the main valuable economic characteristics of alfalfa samples for recommendations for planting in agricultural areas is important for animal husbandry and crop rotation. In the course of the research work carried out, it will be necessary to conduct a study on the unit of feed, hay yield, flowering time and other valuable features of the farm that are important. In the course of our research, 45 varieties and samples were planted and studied, which have been preserved in the alfalfa collection, but have not been studied to this day. As a result of the study, 18 samples showed a negative result, of which 27 out of 45 samples that bloom faster than the template variety Toshkent1 and, in turn, can affect the number of harvests over the calendar year period
Keywords: Alfalfa; collection; seedlings; variety